Methodological Bases and Approaches to Teaching Students to Safety of Life - Kariyeva Halima Ikromjonovna (International Journal on Integrated Education, 2022)
Experience shows that activities to increase the reliability of technical objects, create algorithms for their safe management, develop perfect means and methods of protection against natural, man-made and biological-social emergencies are ineffective without taking into account the human factor. The relevance of the article is due to the need to solve security problems in modern society. Based on the analysis of the literature, the shortcomings of teaching are identified and the need to introduce a number of measures to improve the effectiveness of teaching the subject "Fundamentals of life safety" is substantiated.